2017
DOI: 10.4103/1119-3077.196120
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between international prostate symptom score and uroflowmetry in patients with benign prostatic hyperplasia

Abstract: Correlation between IPSS and Qmax was negative but statistically significant. This implies that an inverse relationship exists between IPSS and Qmax, and remains the only important parameter in uroflowmetry. There was no statistically significant correlation between IPSS and the other variables of uroflowmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
4
17
1
1
Order By: Relevance
“…The findings of this study thus re-enforce the assertion of Bozlu et al [9] that worsening of IPSS is transient in the patients. The result of this research also revealed that the patient sub-group with moderate IPSS values (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) at baseline had a significant increase in mean total IPSS scores 7 days after the biopsy, while those with mild or severe symptoms did not experience a significant change in their symptom score. Voiding dysfunction is defined by an IPSS voiding to storage symptoms ratio of greater than 1.0 [12].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The findings of this study thus re-enforce the assertion of Bozlu et al [9] that worsening of IPSS is transient in the patients. The result of this research also revealed that the patient sub-group with moderate IPSS values (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) at baseline had a significant increase in mean total IPSS scores 7 days after the biopsy, while those with mild or severe symptoms did not experience a significant change in their symptom score. Voiding dysfunction is defined by an IPSS voiding to storage symptoms ratio of greater than 1.0 [12].…”
Section: Discussionmentioning
confidence: 68%
“…This instrument has a set of 7 questions assessing three storage symptoms of frequency, urgency and nocturia, and four voiding symptoms of incomplete emptying, intermittency, weak stream and straining. These are scored from zero to five points with the total IPSS score ranging from 0 to 35 and its symptom severity graded as mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) and severe (20-35). The eighth question in this questionnaire, known as bother score which is scored from zero to six points, evaluates the disease-specific quality of life of the patient [5].…”
Section: Study Protocolmentioning
confidence: 99%
“…Fourth, we used Qmax instead of International Prostate Symptom Score (IPSS) as potential predictors of BPH treatment outcome. However, it has been reported that of the various uroflowmetry parameters (Qmax, average flow rate, and VV), only Qmax is significantly associated with IPSS ( r = −0.368, p < 0.0075) and that Qmax is the only important uroflowmetry parameter (Oranusi et al ., ). Therefore, we think that Qmax as a potential predictor of BPH treatment outcome is an appropriate parameter.…”
Section: Discussionmentioning
confidence: 97%
“…In another meta-analysis study done by Berry et al [8],the prevalence of pathological benign prostatic hyperplasia is only 8 per cent at the fourth decade; however, 50 per cent of the male population has pathological benign prostatic hyperplasia when they are 51 to 60 years old. Study conducted by Oranusi et al [9] reported that average age was 67.2 ± 9.7 (n=51 BPH patients).…”
Section: Discussionmentioning
confidence: 98%